Characterization of static bifurcations in the frequency domain - Itovich, Griselda Rut (2001)
In this paper two-dimensional systems with static bifurcations are considered. An analysis of the bifurcation behavior is proposed using a frequency domain approach. The analyzed bifurcations are known as elementary since they are the building blocks to understand other more complex singularities.